Anscombe's plans for Highrise Living - McCarthy, Christine (Architectural History Aotearoa, 2006)
In the 1930s New Zealand was yet to invest in inner-city living via large scale apartment buildings. Few examples of flats existed. A. Sinclair O'Connor's Courtville (1914-19) at the corner Waterloo Quadrant and Parliament Street, Auckland, and Francis Petre's Manor Place Flats in Dunedin were exceptions to conventional living. In the 1930s greater interest was shown in the design of inner-city apartments – most famously by the Department of Housing Construction's Berhampore Flats, Adelaide Rd (Wellington, Gordon Wilson, 1938-40), and Symonds Street Flats, Symonds Street (Auckland, Friedrich Neumann, 1939-47), anticipating their 1940s work: the Dixon Street Flats, Dixon Street (Wellington, 1940-44), the Maclean Flats, The Terrace (Wellington, 1943-44), the Hanson Street Flats, Newtown (1943-44), and the Greys Avenue Flats, Greys Avenue (Auckland, 1945-47). [NEW PARAGRAPH] In Wellington, Edmund Anscombe dominated the design of privately funded inner city flats, designing six art-deco/modernistic apartments during this time: Belvedere, Hamilton Flats, Olympus, Linfield, Alberts Flats and Franconia. This paper examines these apartments in the context of Anscombe's comments on house design, and housing, and his 1936 proposal to replan the area of Adelaide Road as a residential area to accommodate superblocks of high rise apartments.